Inheritance peculiarities of resistance to Septoria leaf spot on sunflower in F1 hybrids - Levytska, Kh.; Lyakh , V. (Quarantine and plant protection, 2022)
Goal. To find out the peculiarities of inheritance of the resistance level to Septoria leaf spot by sunflower hybrids of the first generation obtained from crossing the lines with different disease resistance. Methods. Field assessment of resistance to pathogen of sunflower breeding lines and F1 hybrids obtained from crossing the lines. Results. Differences in Septoria leaf spot resistance in sunflower breeding lines on a stationary infectious background were found. Among the lines, the most affected by Septoria leaf spot was the line ZL58A and had from 88.8% to 97.9% of plants with symptoms of the disease. ZL70A and ZL78A lines were significantly less affected by desease than the previous line. Healthy plants for two years of research in these samples were from 73.3% to 87.5%. The HAR7 line was close to the previous two lines, the number of diseased plants varied in different years from 16.7% to 40%, and without lesions from 60% to 83.3%. This line had some differences in the intensity of the disease during the two experimental years. As a result of the study, it was found that the hybrid ZL58A × HAR7 was most affected by Septoria leaf spot. The number of affected plants in both years of research ranged from 80.8% to 90.3%. This sample was susceptible to the disease, as well as the maternal line ZL58A. Hybrids of the first generation of the combinations ZL70A × HAR7 and ZL78A × HAR7 were the least affected. In two years of research, these hybrids had between 60% and 79% of healthy plants and 21% to 40% with symptoms of the disease, respectively. These hybrids are relatively resistant to the disease, as well as their maternal and paternal components. Conclusions. The type of inheritance of resistance to Septoria leaf spot by sunflower hybrids is revealed implies the presence of cytoplasmic effects or control of this trait by nuclear genes where susceptibility to the disease is the dominant feature and resistance is recessive.